The Inevitability of Absurdity, or Collective Trance in Boogie-woogie Rhythm: Tom Stoppard’s Play Rosencrantz and Guildenstern are Dead on the Stage of the Old Theatre of Vilnius - Maliutina, Natalia (Literatūra, 2024)
The review discusses aspects of unconventional stage interpretation of Tom Stoppard’s play Rosencrantz and Guildenstern are Dead. The premiere, directed by Yuriy Butusov, took place in September 2023 at the Old Theatre of Vilnius. The play has been interpreted as an open text with numerous intertextual references. The action is organized in the form of separate numbers-scenes, often almost unrelated to each other: dialogues of characters referring to Shakespeare’s Hamlet, to Samuel Beckett’s absurdist drama Waiting for Godot, vocal and dance scenes, musical fragments, acrobatic tricks, performative methods of playing with requisites. The audience’s attention is focused on finding and establishing connections between different elements of the performance, which resembles postmodern bricolage. The symbolic imagery of the production evokes a number of contexts among which the most expressive are mystery-metaphysical and grotesque-visional ones.